Pengembangan Perangkat Pembelajaran E-LKPD Berbuatan Etnosains Berbasis Literasi Sains - Siska Rita Mahyuny; Nursamsu Nursamsu; Hasruddin Hasruddin; Muslim Muslim (Postgraduate, University of Mataram, 2022)
Research activities carry out measurements for science literacy ability contained in ethnoscience values by making electronic Student Work learning tools students worksheets that are useful for students. Ethnoscience is related to the concept of local culture contained in the electronic Student Worksheet learning tool students worksheet which is used as a source of learning and learning activities while science literacy skills will provide motivation and interest in learning in understanding learning materials and improving. Thus the realization of a research objective, namely to determine the feasibility test of material experts, media experts, and practicalization experts from learning tools for the development of students’ worksheet learning tools to carry out ethnoscience based on science literacy on the material for the classification of living things at Muhammadiyah Langsa High School. The research method is a method of product development of students' worksheet learning devices. The results showed that products that have been made and validated by material experts, media experts, and practicalization experts state that the products are suitable for use for sourcing learning media in learning and learning activities of students and teachers. This research can also be concluded that the overall average of expert assessments of students’ worksheet product validation is feasible